Telessaúde com videomodelação no ensino da mãe para o ensino de tato para o filho com TEA - Tozadore, Michele Carnieto (2022)
Parent-mediated training for children with autism can be done by telehealth and is a promising alternative, as treatments can expand to natural settings. The aim of this study was to verify possible contributions of a mother training program, by telehealth with video modeling, to teaching tact to her child with autism. For this, the mother participated in a remote program to teach tact to her 5-year-old son with autism. The program was developed in meetings by the Google meet platform with submission of videos intended for video modeling. The mother's performance was measured by the frequency of correct answers in the predicted behaviors for the organization of the environment, the application of a preference test, the tact training and the completion of the activity. Additionally, the child's frequency of correct answers in the emission of tact, response latency and face deviation were measured. The results indicate that there was an increase in the frequency of correct answers in the mother's behaviors when exposed to training and that the child emitted tact after the mother's training. It is inferred that interventions proposed by telehealth with video modeling can favor the performance of parents in teaching tact to their children with autism.